Mining and natural hazard vulnerability in the Philippines digging to development or digging to disaster? - Holden, William N.; Jacobson, R. Daniel (London Anthem Press, 2012)
"This book explores how natural hazards in the Philippines can amplify the environmental harm prevalent in mining and pose a substantial threat to the livelihoods of archipelago's poor, who depend upon subsistence agriculture and subsistence aquaculture."--Publisher's description.
Includes bibliographical references (pages 251-275) and index.
Keywords: Mineral industries -- Environmental aspects -- Philippines; Mines and mineral resources -- Environmental aspects -- Philippines; Natural disasters -- Philippines; Mine accidents -- Philippines; Environmental risk assessment -- Philippines